THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION PT. MAYBANK INDONESIA FINANCE JAKARTA BRANCH - Hendri Hendri; Budi Haryono; Saparso Saparso (ID Solutions, 2021)
This study discusses the effect of service quality on customer loyalty mediated by customer satisfaction at PT. Maybank Indonesia Finance Jakarta Branch. This research was conducted by using purposive sampling. Data analysis using Smart PLS analysis. The results of the analysis conclude that service quality does not affect customer loyalty. So it can be said, good service quality may not necessarily make the customer loyal to PT. Maybank Indonesia Finance because there are still several factors that can make customers loyal. Service quality has a positive and significant effect on customer satisfaction. So it can be said, good service quality will increase customer satisfaction with PT. Maybank Indonesia Finance. Customer Satisfaction has a positive and significant influence on Customer Loyalty. So it can be said, increasing customer satisfaction will make customers more loyal to PT. Maybank Indonesia Finance. Customer satisfaction can mediate the effect of service quality on customer loyalty. So it can be said, if the quality of service provided is getting better, it will form high customer satisfaction in the minds of customers, then this will further increase customer loyalty at PT. Maybank Indonesia Finance.